Online Resources in Pediatric Surgery: The New Era of Medical Information - Raigani, Siavash; Numanoglu, Alp; Schwachter, Marc; Ponsky, Todd A. (European Journal of Pediatric Surgery, 2014)
Tele-education has the potential to facilitate rapid sharing and dissemination of current research and knowledge among pediatric surgeons around the world. Classically, the exchange of surgical research occurred via national surgical conferences, articles published in peer-reviewed journals, and textbooks. The advent of Web 2.0 and the rapid pace of technologic advancement have allowed knowledge, education, and research to be exchanged online. Virtual symposiums act as online conferences where participants present and debate new research and surgical techniques in real-time web meetings. Resource libraries allow up-to-date information to be archived and viewed at the user's convenience, bypassing the need to wait long periods for paper publications. Tele-education allows pediatric surgeons to connect and share ideas around the world, while saving time and money.
Keywords: pediatric surgery; tele-education; virtual symposium; webinar